2014
DOI: 10.5603/kp.a2014.0133
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical left atrium remodelling in patients with frequent premature ventricular contractions

Abstract: Frequent PVCs are associated with larger LAV and trapezoidal LA shape in otherwise healthy patients, suggesting LA remodelling in response to increased LV filling pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 18 publications
(20 reference statements)
2
27
0
Order By: Relevance
“…Compatible with the previous study, PALS was lower in patients with RVOT‐fVES and pEF . Two previous studies found increased LA volume or indexes in patients with fVES and with normal ejection fractions . Unlike these studies, LAVI was not different between patients and controls in our study; this finding suggested that PALS and AED may be affected before left atrial enlargement occurs in patients with RVOT‐fVES and pEF.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Compatible with the previous study, PALS was lower in patients with RVOT‐fVES and pEF . Two previous studies found increased LA volume or indexes in patients with fVES and with normal ejection fractions . Unlike these studies, LAVI was not different between patients and controls in our study; this finding suggested that PALS and AED may be affected before left atrial enlargement occurs in patients with RVOT‐fVES and pEF.…”
Section: Discussionsupporting
confidence: 56%
“…We concluded that PALS and AED were deteriorated in patients with fVES, which were shown as risk factors for AF development in previous studies . It has been shown that incidence of new‐onset AF is higher in patients with multiform fVES .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“… b Represents the follow-up period range using mean/median years (or months [mo] when indicated). References not reporting the follow-up timeframe [ 36 , 44 , 48 , 55 , 62 , 63 , 65 , 82 , 91 , 93 ]. Details on follow-up period for all studies are available in S3 Table .…”
Section: Resultsmentioning
confidence: 99%
“…HRV analysis, in time or frequency domain, is a reliable, noninvasive method for the assessment of autonomic functions, by several parameters currently used to characterize the physiological spontaneous fluctuations in heart rate (HR) and normal R-R intervals [ 10 ]. This method is used in physiological models and various pathological states, for the assessment of cardiovascular risk [ 11 , 12 , 13 ]. Certain parameters as the root mean square of the successive differences (RMSSD) and high-frequency power (HF) characterize mainly the PNS function [ 14 ].…”
Section: Introductionmentioning
confidence: 99%